1985
DOI: 10.1002/ajmg.1320220224
|View full text |Cite
|
Sign up to set email alerts
|

Chorionic villi sampling: Women's attitudes

Abstract: To determine the acceptability of chorionic villi sampling (CVS) to women eligible for prenatal diagnosis, we undertook a survey to identify aspects of this new procedure that made it more or less preferable than amniocentesis. All women greater than or equal to 35 years scheduled for amniocentesis were asked to read some detailed descriptive material about amniocentesis and CVS, to rate the importance of the specific differences between procedures, and to indicate which procedure they would prefer, first cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

1988
1988
2001
2001

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 10 publications
(3 reference statements)
1
18
0
Order By: Relevance
“…For similar reasons, other researchers have also found that a substantial percentage of women prefer prenatal testing to be conducted in the first trimester. [21][22][23][24] Earlier studies regarding second-trimester MSAFP testing found that women would prefer serum screening, because it would allow a stepwise approach to prenatal diagnosis, despite the limited time frame for decision-making. [25][26][27] Almost all of the women reported that they would have subsequent invasive testing if the maternal blood test returned an abnormal result.…”
Section: Resultsmentioning
confidence: 99%
“…For similar reasons, other researchers have also found that a substantial percentage of women prefer prenatal testing to be conducted in the first trimester. [21][22][23][24] Earlier studies regarding second-trimester MSAFP testing found that women would prefer serum screening, because it would allow a stepwise approach to prenatal diagnosis, despite the limited time frame for decision-making. [25][26][27] Almost all of the women reported that they would have subsequent invasive testing if the maternal blood test returned an abnormal result.…”
Section: Resultsmentioning
confidence: 99%
“…CVS is optimally performed, either transcervically or transabdominally, a t 9 to 12 menstrual weeks. Also, because results from assays of villi can be reported more rapidly, the traditionally difficult aspects of the waiting period may be if not eliminated, at least substantially shortened [Chervin et al, 1977;Golbus et al, 1974;Lippman et al, 1985;Tunis, 1985;Verjaal et al, 19821. Much clinical experience and research support the psychological advantage of shortening the time couples must wait for prenatal diagnosis results.…”
Section: Chorionic Villus Samplingmentioning
confidence: 98%
“…A 7-center collaborative investigation was sponsored by the National Institute of Child Health and Human Development (NICHD) beginning in 1985 to examine the safety and accuracy of CVS compared to amniocentesis [Hogge et al, 1985;Lippman et al, 1985;NICHD, 1976;Rhoads et al, 19891. The present paper results from this investigation and describes an empirical comparison of mood states, over the course of pregnancy, of women who had amniocentesis with those who had CVS.…”
Section: Purpose Of Present Studymentioning
confidence: 99%
“…Premarital screening has been recently made compulsory in Lebanon; however, there are currently no data concerning the effects of genetic counselling and acceptance of prenatal diagnosis in countries such as Lebanon. In fact, most studies have been conducted in North America and Europe and show high levels of uptake of prenatal diagnostic procedures (Modell et al, 1984;Lippman et al, 1985;Perry et al, 1985;McGovern et al, 1986;Cao et al, 1987;Cox, 1987, 1988), but this might not be the case in Middle-Eastern societies, because of different cultural and religious beliefs. Lebanon is a mosaic of different religious communities, of various educational and socioeconomic backgrounds.…”
Section: Introductionmentioning
confidence: 99%